Mas democracia en America Latina: democratizacion y consolidacion de la democracia en una perspectiva comparada - Nohlen, Dieter (Estudios sociales, 1989)
Bewitched by the impact of the Greek, Spanish, and Portuguese political evolutions, many political analysts thought they had found a definite and reliable paradigm for the study of political transition. However, through time, new evidence has proved that, despite its similarities, the peculiarities of each case do not allow oversimplified generalizations. The recent Latin American experiences seem to corroborate the difficulties of a general theory on such a matter. Comparative analysis seems to provide a suitable alternative of political interpretation
Keywords: Lateinamerika